Economic programmes and poverty reduction: NGO experiences from Tamil Nadu - Rajasekhar, D. (2002)
This paper analyses the impact of the economic programmes of SHARE, an NGO in Tamil Nadu, on poverty reduction, with the help of data collected from the households of 84 women members. The economic programmes contributed to savings and income increase for the women. However, the member group was not found to be significantly different from the comparison group in terms of control over income and decision-making. - Reproduced.
Keywords: Poverty - India - Tamil Nadu; Poverty